PELATIHAN PENINGKATAN PRODUKTIVITAS UMKM DI ERA REVOLUSI INDUSTRI 4.0 - Rosnaini Daga, Rosnaini; Salam, Karta Negara; Muhammad, Natsir; Alwi, Aulia; Rosyadah, Khairina; B, Ceskakusumadewi; Wahyuningsih, Wahyuningsih (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The era of the industrial revolution 4.0 gave rise to opportunities and challenges for business actors, especially MSMEs, which have made a major contribution to the Indonesian economy. However, the readiness of MSMEs in responding to the dynamics and developments in the business environment is still lacking. The low mastery of technology for MSMEs makes MSMEs very limited in marketing their products. This community service activity was carried out at the Productivity Improvement Center (BPP Kendari) office and was attended by 75 MSME actors from Kendari City. To provide an understanding of the Industrial Revolution 4.0, the opportunities and challenges that arise, and how to respond to existing phenomena. This activity also aims as a medium for exchanging information and experiences for MSMEs in running their business. Business transformation is an important keyword in responding to the changes that occur. Apart from that, increasing knowledge and skills such as people management, collaboration and negotiation skills, creativity, critical thinking, and emotional intelligence are other solutions that must be owned in order to survive and compete in the existing business environment. In the industrial era 4.0, MSMEs must be able to adapt to technology, because only MSMEs that are able to adapt can survive. In addition, MSMEs must be able to improve their quality, must be more productive in order to survive